Analisis Implementasi Metode Hilah Dalam Ushul Fikih Ekonomi Pada Aktivitas Akad Jual Beli Sanda di Kabupaten Serang Banten (Studi: Kampung Kejaban Kepandean Ciruas Serang Banten) - Syam, Surya Darma; Nursaman, Nursaman (Syi`ar Iqtishadi : Journal of Islamic Economics, Finance and Banking, 2024)
Rasulullah SAW, forbade conditional buying and selling. However, in Kepandean Village, Ciruas Subdistrict, Serang Regency, Banten, there was a sale and purchase which was carried out using conditions agreed upon by both parties called the Sanda sale and purchase. This study aims to describe and analyze the implementation of the hilah method in Buying and Selling Sanda in Kepandean Village, Ciruas District, Serang Regency, Banten. The method used is descriptive with qualitative data. Data collection techniques using library research and interviews. With a community law approach (law in society approach) and a conceptual approach (conceptual approach). The discussion material in this paper includes hilah, buying and selling and sanda contracts. The results of this study can be concluded that in the implementation of the hilah method in the Sale and Purchase of Sanda in Kepandean Village, Ciruas District, Serang Banten Regency, namely the seller comes directly to people who are considered to have more assets and are able to buy land or other valuable items offered in the form of an agreement, on condition that -conditions set based on 'urf (custom). Quoting Max Weber's theory of practical rationality, which views that all human activities in this world are always associated with pragmatism and egotism, this practice can be understood, namely that both parties want convenience and practicality. Then there is a party in power (superior) taking action against the weak.